Smart Mesh Networking City by New Method - Sivakumar, D.; Legapriyadharshini, N. (Asian Journal of Engineering and Applied Technology, 2017)
Current Trend in Networking is Wireless Mesh Networking (WMN) that makes rural village, a smart city (Mesh City) with their new technical infrastructure and characteristics. Wireless Mesh Networking provide excellent broad band connection to the rural region for making rural smart city. Although several planning is carried for mesh networking using various Protocols, Algorithms in this paper we design a new method with low cost network deployment in rural regions.